2019
DOI: 10.1186/s10194-019-0971-6
|View full text |Cite
|
Sign up to set email alerts
|

Real world preventative drug management of migraine among Spanish neurologists

Abstract: BackgroundMany different preventatives have showed efficacy in the treatment of migraine. National guidelines differ in their recommendations and patients’ characteristics are usually taken into account in their selection. In Spain, real life use of preventive therapies seems to be heterogeneous. We aimed to evaluate differences in clinical practice and adherence to national guidelines among Spanish neurologists.MethodsObservational descriptive study. A survey was conducted among neurologists ascribed to the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…The PREEMPT trials demonstrated the efficacy and safety of OnabotA as a preventive for 56 weeks treatment in CM [ 5 , 12 , 13 ]. The COMPEL study confirmed these results and provided data up to 108 weeks [ 28 ] and further real-life studies corroborated these previous conclusions [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 74%
“…The PREEMPT trials demonstrated the efficacy and safety of OnabotA as a preventive for 56 weeks treatment in CM [ 5 , 12 , 13 ]. The COMPEL study confirmed these results and provided data up to 108 weeks [ 28 ] and further real-life studies corroborated these previous conclusions [ 26 , 29 ].…”
Section: Discussionsupporting
confidence: 74%
“…Sodium valproate was reserved as a second-line approach, as its use is off-label in Italy. The choice of antidepressants and antiepileptics as a first-line therapy was reserved for patients with more severe and chronic migraine, according to previous studies [21,22]. The use of magnesium in 64 patients as a preventive treatment deserves proper discussion.…”
Section: General Considerations Regarding Headache Populationsmentioning
confidence: 99%
“…Treatment recommendations for migraine clearly document when a preventive treatment should be initiated, as well as specific recommended medications that should be prescribed [8][9][10][11][12] . However, original findings from the American Migraine Prevalence and Prevention study estimated that only 13% of all patients with migraine received PMM, and an estimated 39% were appropriate candidates for PMM 3 .…”
Section: Introductionmentioning
confidence: 99%